Upaya Peningkatan Kebugaran Jasmani Siswa Melalui Permainan Tangkak Rani : Tangan Merangkak Kebugaran Jasmani - Didit Kurniawan; Mochammad Ridwan; Muhammad Bambang Herinanta (Journal of Creative Student Research, 2024)
This research aims to assess the impact of traditional games on enhancing students' physical fitness by modifying the traditional game Tangkak Rani (Physical Fitness Crawling Hands) for class X TAV-3 students at SMKN 3 Surabaya. The study follows a PTKK design, conducted over three cycles, involving a sample of 34 students from class X TAV-3. Initially, the modified TKJI test revealed that 18 students completed the pre-cycle assessment, equating to a completion rate of 52.93%. In response, the researcher implemented modifications to the Tangkak Rani game, resulting in 23 students meeting the KKM, with a percentage of 57.65%. However, this did not reach the desired goal of more than 27 students completing the assessment, prompting a second cycle. Following this action, 28 students completed the test, yielding a completion rate of 82.36%. These findings indicate a positive effect of traditional game modifications on the physical fitness of class X TAV-3 students at SMKN 3 Surabaya.